NON-CONTRIBUTORY PENSION SCHEME AND THE WELFARE OF RETIRED CIVIL SERVANTS IN EBONYI STATE, NIGERIA (2015)
Pensioners in Nigeria face enormous challenges accessing their retirement benefits in the non-contributory pension scheme, which has negatively impacted on their welfare. This necessitated the introduction of contributory pension scheme in 2004. Ebonyi State is one of the states that are still operating the non-contributory pension scheme in Nigeria despite the challenges. A lot of studies on non-contributory pension scheme focused on corruption associated with the management of the scheme without examining other challenges and their effects on retirees’ welfare. This study, therefore, examined the challenges and adequacy of the non-contributory pension scheme on the welfare of retired civil servants in Ebonyi State, Nigeria. Social Exchange and Structural Functionalist theories provided the framework. Survey design was employed. Simple random sampling technique was used to select 400 retired civil servants out of 4,149 retirees on the payroll as at 2011 and 24 staff of pension department in the office of the Head of Service, 68 staff of Sub-Treasury in the office of the Accountant General spread across the 13 local government areas in Ebonyi State and 16 staff of Ebonyi State Audit where pensions are processed. Two sets of semi-structured questionnaire were used to collect data on demographic characteristics of respondents, adequacy of pensions in meeting retirees’ welfare needs, retirees’ coping strategies and challenges in the management of non-contributory pension scheme. In-depth interviews were conducted with three executive of the union of retired pensioners, six government officials, and two pensioners. Descriptive and inferential statistics (Chi-square at p < 0.05%) were used to analyse quantitative data while qualitative data were content analysed. The respondents’ age was 55.2 ± 12.5 years, 69.7% were males while 26.2% had first degrees. About 80% of the retirees indicated that their pensions were not adequate in meeting their major welfare needs such as accommodation, adequate diet, health services and education for children. The most widely adopted coping strategies by retirees were investment of gratuities (45.5%) and relocation to family houses (32.3%). Major challenges faced by non-contributory pension scheme were lack of biometric data capturing machine (81.2%), high workload on staff processing pensions (61.2%), poor funding by the government (75.3%) and mismanagement of pension funds (54.2%). There was no significant relationship between monthly pensions of retirees and their welfare provisions (X2 = 4.07). There was a positive relationship between monthly pensions of retirees and their household size (X2 = 52.91). There was a significant relationship between educational qualifications of retirees and their monthly pension distribution (X2 = 379.13). Inadequate preparations for retirement adversely affected the welfare of retirees, delay in the payment of retirement benefits, misappropriation of pension funds, bureaucratic delays and governments’ unwillingness to review pensions were challenges confronting the non-contributory pension scheme. Non-contributory pension scheme was inadequate in meeting retirees’ welfare needs in Ebonyi State. There is the need to restructure the management of the non-contributory pension scheme in order to meet the needs of retirees in Ebonyi State.